Force decay evaluation of latex and non-latex orthodontic intraoral elastics: in vivo study - Daniela Ferreira de Carvalho Notaroberto; Mariana Martins e Martins; Maria Teresa de Andrade Goldner; Alvaro de Moraes Mendes; Cátia Cardoso Abdo Quintão
ABSTRACT Objective: This clinical study was conducted in order to evaluate force decay over time of latex and non-latex orthodontic intraoral elastics. Methods: Patients (n = 15) were evaluated using latex and non-latex elastics in the periods of : 0, 1, 3, 12 and 24 hours. The rubber bands were transferred to the testing machine (EMIC DL-500 MF), and force values were recorded after stretching the elastic to a length of 25mm. Paired t test was applied and analysis of variance (ANOVA) was used to evaluate the variation of force generated. LSD (Fisher's least significant difference) post-hoc test was thus employed. Results: As regards the initial forces (zero time), the values of force for non-latex elastic were slightly higher than for the latex elastic. In the subsequent times, the forces generated by the latex elastic showed higher values. Regarding the material degradation, at the end of 24 hours the highest percentage was observed for non-latex elastic. Conclusions: The latex elastics had a more stable behavior during the studied period, compared with non-latex.